1985
DOI: 10.1111/j.1476-5381.1985.tb08869.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the combined administration of β‐adrenoceptor antagonists and non‐steroidal anti‐inflammatory drugs on ligation‐induced arrhythmias in rats

Abstract: Pretreatment of anaesthetized rats with intravenously administered β‐adrenoceptor antagonists or non‐steroidal anti‐inflammatory drugs (NSAIDs) reduced the incidence and severity of ventricular arrhythmia which resulted from acute coronary artery ligation. The β‐adrenoceptor antagonists preferentially suppressed the immediate (Phase 1A) arrhythmia while the NSAIDs suppressed the delayed (Phase IB) arrhythmias. Combined administration of β‐adrenoceptor antagonists and the NSAIDs produced a more pronounced antia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Interestingly, some NSAIDs have been shown to reduce the risk of ventricular arrhythmias in experimental models of ischaemia. The NSAIDs used in those studies included indomethacin, ketoprofen and mefenamic acid [76–79]. Studies on ibuprofen, conducted in both animals and humans, have shown conflicting results [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some NSAIDs have been shown to reduce the risk of ventricular arrhythmias in experimental models of ischaemia. The NSAIDs used in those studies included indomethacin, ketoprofen and mefenamic acid [76–79]. Studies on ibuprofen, conducted in both animals and humans, have shown conflicting results [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have identified meclofenamate as a potent TRPM4 inhibitor using a thallium‐based screening (Vandewiele et al., 2022). Remarkably, previous research has reported that intravenous administration of 3 mg/kg meclofenamate can reduce ventricular arrhythmias induced by coronary artery ligation in anaesthetised rats (Fagbemi, 1984, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Pharmacologically, the effect of blocking or activating the different adrenergic receptors in rats is ambiguous. Although β-adrenergic stimulation by isoprenaline is proarrhythmic, 53 blocking the β-adrenergic receptors have yielded both positive 35,104 -106 and negative results. 26,107 -109 Some investigators believe that the antiarrhythmic effect of β-blocking agents sometimes observed in rats is due to blockage of cardiac-β adrenergic receptors, 105 and others have suggested that the antiarrhythmic properties are due to peripheral effects, for example, increasing levels of serum K + 110 or neurokinin activity.…”
Section: Interventions Applied To Rat Models Of Vf Caused By Amimentioning
confidence: 99%